Starter Aiding System Based on Supercapacitors for the LDE2100 Locomotive - Kertész, Csaba Zoltán; Borza, Paul Nicolae (IEEE, 2009)
The paper presents an intelligent embedded system designed for aiding the starting process of the internal combustion engine of the LDE2100 locomotive. The system uses supercapacitors to reduce the strain on the main batteries increasing battery life. The higher charged supercapacitors also offer a higher degree of successful engine starts. Another advantage of the proposed system is the use of solid state relays instead of the electropneumatic ones, greatly reducing transient voltages and current spikes, the main causes of shortened lifespans of traditional engine starting systems.